Turbulence/outflows perpendicular to low-power jets in Seyfert galaxies. Issue Volume 15:Issue S359(2020) (March 2019) - Venturi, Giacomo; Marconi, Alessandro; Mingozzi, Matilde; Cresci, Giovanni; Carniani, Stefano; Mannucci, Filippo
Abstract: We present recent results from our MAGNUM survey of nearby active galactic nuclei (AGN), which exploits observations from the optical/near-IR integral field spectrograph MUSE at VLT. We detect strongly enhanced line widths in emission line maps of four galaxies perpendicularly to their low-power jets and AGN ionisation cones, indicative of turbulent/outflowing material. The observation of a similar phenomenon in other works suggests that it originates from an interaction mechanism between the jet and the galaxy disc through which it propagates.